PROTECTION OF THE RIGHT TO RESPECT FOR PRIVATE LIFE IN THE COURSE OF EDUCATIONAL ACTIVITIES IN THE PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Fomina L. Yu. (Scientific Journal of Pedagogy and Economics, 2021)
The development of digitalization processes and their implementation in educational activities, the establishment of certain legal and ethical requirements for its participants determine the importance of ensuring privacy, identifying and preventing the actions that can be considered as interference with it, and specifying the limits of admissibility of such interference. The purpose of the article is to identify, analyze and generalize the rulings of the European Court of Human Rights regarding the protection of the right to respect for private life in relation to educational activities. Conclusions were made about broad understanding of private life and interference with it by the European Court of Human Rights in the framework of educational activities. It was pointed out that its content includes questions related to the teacher’s professional activity, the compliance of the participants in the educational activity with certain requirements for appearance and behavior, and control over their behavior using modern technologies. It was revealed that interference with private life in the course of educational activities is possible provided that certain criteria for its admissibility, connected with both moral attitudes of the subjects of such activities and with the developed international standards, are met.